"The Videos Gave Weight to Our Work": Animated mHealth Videos and Tablet Technology Boost Community Health Workers' Perceived Credibility in Khayelitsha, South Africa. (July 2022) - Adam, Maya; Job, Nophiwe; Mabaso, Bongekile; Bärnighausen, Till; Kuhnert, Kira-Leigh; Johnston, Jamie; Mqungwana, Neliswa; Le Roux, Ingrid; Mbewu, Nokwanele; Gates, Jennifer; Scott, Kerry; Vandormael, Alain; et al.
Mobile health (mHealth) interventions are increasingly used to support community health workers (CHWs) in low-and middle-income countries. As near-peers within their communities, the credibility of CHWs is sometimes questioned—a recognized barrier to their efficacy. Nested within a large, randomized-controlled trial, this qualitative study captured the experiences of South African CHWs, called "Mentor-Mothers, " using tablets and animated videos to promote exclusive breastfeeding. We conducted in-depth telephone interviews with 26 tablet-carrying Mentor-Mothers. We analyzed interview transcripts using a Grounded Theory approach, then developed a theoretical framework, based on an emerging theme, for understanding how tablet technology boosts the perceived credibility of CHWs. Tablet-carrying Mentor-Mothers described an increase in their perceived credibility, which they attributed to overt and signaling effects related to enhanced credibility of (1) their messages, (2) themselves as messengers, and (3) the program employing them. Mobile technology investments in CHWs could enhance their credibility, translating into meaningful investments in the health of under-served communities.